Efectos locales de las secreciones externas de Sphaerobothria hoffmanni (Araneae : Theraphosidae) de Costa Rica - Herrero, Marco V. (1984)
The local effects induced as a consequence of applications of four external secretions from the spider Sphaerobothria hoffmanni were recorded. Macroscopic lesions were not found; the only local effect microscopically of served was a weak necrosis in the skeletal muscle in mice.